Aplikasi Simple Hand Washing Station terhadap Perilaku Cuci Tangan dalam Pencegahan Penularan Covid-19 di Desa Dilem Kecamatan Kepanjen: Application of Simple Hand Washing Station on Handwashing Behavior in Covid-19 Transmission Prevention in Dilem Village, Kepanjen District - Wahyudi, Yuyud; Nengrum, Lilis Sulistiya; Anggreyanti, Icca Presilia (Borneo Journal of Medical Laboratory Technology, 2021)
Coronavirus Disease 2019 (COVID-19) is a pandemic that is now a global threat where this virus causes many people to die every day in various countries, one of which is Indonesia, this disease is caused by SARS-CoV-2. The many impacts caused by COVID-19 make Simple Handwashing Station (SHS) one of the prevention efforts that can build proper handwashing behavior. Based on the results of research conducted from 13-18 April 2020 which is divided into 4 strategic points in Dilem Village. This study uses a Quasi-experimental research design with a One Group Pre Post-test design approach with a sample of residents of Dilem Village precisely RT 5 and 6 RW 1 Lemah Dhuwur. The analysis technique uses Paired Sample T-Test with the results that show that there is an influence of the application of simple handwashing station on the proper handwashing behavior of the residents of Dilem Village with a P-value <0.05, based on these results it can be concluded that there is an effect of the application of simple hand washing station for handwashing behavior in preventing COVID-19 transmission in Dilem Village Kepanjen District, with this result it is expected to be able to add a simple handwashing station in several other strategic points in Dilem Village in COVID-19 prevention.